Obstetric admissions to the critical care unit: a one year experience at a tertiary care referral centre of the developing country - Agarwal, Kriti; Mukhopadhyay, Partha; Dahiya, Krishna; Hooda, Reetu; Sanghi, Sahil; Narsaria, Kamal; Garg, Gazal (International Journal of Medicine, 2017)
Background: Care of the critically ill pregnant women presents a unique challenge as the assessment, monitoring and the treatment must take into account both maternal and fetal wellbeing as well as physiological changes of pregnancy.Objective: To assess the indications for critical care unit transfer of obstetric and postpartum cases and describe the profile and feto-maternal outcomes of such patients.Methods: This prospective observational study was conducted in department of Obstetrics and Gynaecology of Medical College and Hospital, Kolkata from 1st May 2013 to 30th April 2014.Total 50 cases were included and data was analysed by frequency, percentage, paired and unpaired t test, chi square test and test of equality of proportions using SPSS version 20.Results: 0.9% of total obstetric and postpartum admissions required critical care facilities and contributed to 16.67% of CCU admissions. Mean age of patients included in our study was 25.4 years. Most of the patients were admitted antepartum (n=37, 74%) with mean gestational age at admission being 34.2703+6.85018 weeks. More patients presented with obstetric complications (74%, n=37) as compared to medical complications (26%, n=13). The most common indication for admission were major haemorrhage (n=18, 36%) and hypertensive disorders of pregnancy (n=17, 34%). There were 16(32%) maternal deaths. MODS (31.25%) and hypovolemic shock (18.75%) were the most common causes of maternal death in our study. Conclusion: The overall mortality was high, emphasizing the need for dedicated obstetric high dependency units.